ANALISIS FOKUS KONSENTRASI ATLET DALAM MENGHADAPI SITUASI KOMPETITIF PADA ATLET SEPATU RODA KARAWANG - Nabilahasha, Anggi; Setiawan, M. Arief; Wijaya, Habibi Hadi (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to analyze the level of focus and concentration of Karawang roller skaters in facing competitive situations and identify the internal and external factors that influence it. Using a descriptive quantitative approach, data were collected through a questionnaire from 30 athletes who passed the 2024 West Java PIN selection. Analysis was conducted using SPSS version 26 through descriptive statistical tests and instrument validity and reliability. The results showed that the athletes' level of focus and concentration was in the high category with an average score of 4.23. The indicators